Crustal vertical deformation of Amazon Basin derived from GPS and GRACE/GFO data over past two decades - Jun Fang (KeAi Communications Co., Ltd., 2021)
In this study, the Gravity Recovery and Climate Experiment (GRACE) satellite observations, combining 71 continuous Global Positioning System (CGPS) data, are used to detect surface vertical loading deformation of the Amazon Basin during 2002–2020. The results show that the maximal annual amplitude of the surface mass changes derived by GRACE is more than 80 cm in terms of the equivalent water height (EWH) in the Amazon Basin. Most part of Amazon experiences mass gain, especially the Amazon River, while there is little mass loss in the northern and eastern parts. Through the Pearson correlation analysis, the monthly de-trended time series of GPS-observed vertical deformation and GRACE-derived mass loading are in good agreement with an average correlation coefficient of about 0.75 throughout the Amazon region. The common seasonal signals of GPS vertical displacements and GRACE/GFO loading deformations are extracted using the stack averaging. The two kinds of common seasonal signals show a good consistency, and together indicate approximate 20 mm peak-to-peak seasonal amplitude. Strong annual variations are identified both in the monthly GPS and GRACE/GFO data by the wavelet analysis. However, the time-frequency spectrum of GPS has more signal details and more significant semi-annual variations than that of GRACE/GFO. These results may contribute to the understanding of secular crustal vertical deformation in the Amazon Basin.